Sensing of Porcine Reproductive and Respiratory Syndrome Virus-Infected Macrophages by Plasmacytoid Dendritic Cells - García-Nicolás, Obdulio; Auray, Gaël; Sautter, Carmen A.; Rappe, Julie C. F.; McCullough, Kenneth C.; Ruggli, Nicolas; Summerfield, Artur (Frontiers in Microbiology, 2016)
Porcine reproductive and respiratory syndrome virus (PRRSV) represents a macrophage (MØ)-tropic virus which is unable to induce interferon (IFN) type I in its target cells. Nevertheless, infected pigs show a short but prominent systemic IFN alpha (IFN-α) response. A possible explanation for this discrepancy is the ability of plasmacytoid dendritic cells (pDC) to produce IFN-α in response to free PRRSV virions, independent of infection. Here, we show that the highly pathogenic PRRSV genotype 1 strain Lena is unique in not inducing IFN-α production in pDC, contrasting with systemic IFN-α responses found in infected pigs. We also demonstrate efficient pDC stimulation by PRRSV Lena-infected MØ, resulting in a higher IFN-α production than direct stimulation of pDC by PRRSV virions. This response was strain-independent, required integrin-mediated intercellular contact, intact actin filaments in the MØ and was partially inhibited by an inhibitor of neutral sphingomyelinase. Although infected MØ-derived exosomes stimulated pDC, an efficient delivery of the stimulatory component was dependent on a tight contact between pDC and the infected cells. In conclusion, with this mechanism the immune system can efficiently sense PRRSV, resulting in production of considerable quantities of IFN-α. This is adding complexity to the immunopathogenesis of PRRSV infections, as IFN-α should alert the immune system and initiate the induction of adaptive immune responses, a process known to be inefficient during infection of pigs.